Management of public institutions - Andreea Daniela Giucǎ; Ileana Lucica Bota; Vili Dragomir (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The study addresses the issue of the management of public institutions in Romania by reviewing the main approaches presented in the specialized literature. The research identifies and describes the characteristics and functions of the management of public institutions as well as the main management systems used in the public management process.
Keywords: H11; H61; 330; management; public institutions; public sector; Romania